ZnO/CdS Bilayer used for Electrode in Photovoltaic Device - Chien, Dang Tran; Long, Pham Duy; Hoi, Pham Van (Communications in Physics, 2011)
In this article we present the fabrication and characterization of the nanoporous ZnO and/or ZnO/CdS thin films onto indium doped-tin oxide (ITO) substrates, based on the thermal evaporation technique followed by thermal treatment. The preparation method was relatively simple and low-cost for large scale uniform coating to produce clean, dense and strong adhesion to substrate thin films. The nanostructured ZnO and ZnO/CdS thin films were characterized by X-ray diffraction (XRD) and field emission scanning electron microscope (FE-SEM). The nanostructured ZnO/CdS bilayer film was used in a photo-electrochemical (PEC) cell as a working electrode and a Pt net as a counter electrode. The results show that the photovoltaic cell with nanostructured ZnO/CdS bilayer film electrode has significantly improved photoelectric capability in comparison with that of ZnO electrode.